Pre-classification method for detecting vegetation cover changes in Dak Lak province (Vietnam) - Trinh, Le Hung; Le, Van Phu; Nguyen, Thi Thu Nga (Bulletin of Geography. Physical Geography Series, 2025)
In recent years, the process of socio-economic development and population growth have negatively affected the vegetation cover in the Central Highlands region of Vietnam, leading to a decline in forest cover area and quality. This article presents the results of monitoring and detecting the changes in vegetation cover in Dak Lak province (Vietnam) from Landsat image data for the period 2000–2020. Three Landsat image scenes, including Landsat TM images taken in March 2000, February 2010 and Landsat 8 OLI images taken in February 2020 were used to calculate the Normalized Difference Vegetation Index (NDVI); then, the NDVI value was classified into five ranges: NDVI ≤ ˗0.2, ˗0.2 < NDVI ≤ 0, 0 < NDVI ≤ 0.2, 0.2 < NDVI ≤ 0.4, 0.4 < NDVI ≤ 0.6 and NDVI > 0.6. The NDVI differencing and thresholding methods are used to evaluate spatio-temporal changes in vegetation cover quality in three categories (decreasing, increasing and no-change) during the research period. The results show that there is a significant change in the vegetation cover for the period 2000–2020. Among them, the majority vegetation cover with decreased quality is natural forest, while the vegetation areas with increased quality are mainly planted forests and industrial trees. The results received in the study provide objective and timely information, helping managers in monitoring and protecting forest resources.